Investigation of receptor binding and functional characteristics of hemopressin(1–7). (August 2016) - Dvorácskó, Szabolcs; Tömböly, Csaba; Berkecz, Róbert; Keresztes, Attila
Abstract: The orally active, α-hemoglobin derived hemopressin (PVNFKFLSH, Hp(1–9)) and its truncated (PVNFKFL, Hp(1–7) and PVNFKF, Hp(1–6)) and extended ((R)VDPVNFKFLSH, VD-Hp(1–9) and RVD-Hp(1–9)) derivatives have been postulated to be the endogenous peptide ligands of the cannabinoid receptor type 1 (CB1). In an attempt to create a versatile peptidic research tool for the direct study of the CB1 receptor–peptide ligand interactions, Hp(1–7) was radiolabeled and in vitro characterized in rat and CB1 knockout mouse brain membrane homogenates. In saturation and competition radioligand binding studies, [ 3 H]Hp(1–7) labeled membrane receptors with high densities and displayed specific binding to a receptor protein, but seemingly not to the cannabinoid type 1, in comparison the results with the prototypic JWH-018, AM251, rimonabant, Hp(1–9) and RVD-Hp(1–9) (pepcan 12) ligands in both rat brain and CB1 knockout mouse brain homogenates. Furthermore, functional [ 35 S]GTP γS binding studies revealed that Hp(1–7) and Hp(1–9) only weakly activated G-proteins in both brain membrane homogenates. Based on our findings and the latest literature data, we assume that the Hp(1–7) peptide fragment may be an allosteric ligand or indirect regulator of the endocannabinoid system rather than an endogenous ligand of the CB1 receptor. Highlights: The radiolabelled hemopressin(1–7) was expected to show cannabinoid receptor activity at the CB1 receptor. However, the radioligand hemopressin(1–7) demonstrated a CB1-independent binding in wild type rat brain and CB1-KO mouse brain membrane homogenates. Both hemopressin(1–7) and hemopressin(1–9) showed competitive binding with similar affinity values in both tissue homogenates. Hemopressin(1–7) and hemopressin(1–9) poorly activated G-proteins in both tissue homogenates. Thus, the radioligand hemopressin(1–7) is supposed to be a regulator of the endocannabinoid system rather than an endogenous ligand of the CB1 receptor.